A bimetallic nanocatalyst for light-free oxygen sensitization therapy - Xia Guo; Hongwei Liao; Jiaming Tian; Chuang Yang; Fan Xia; Wenshi Liang; Nan Wang; Pin Li; Bo Zhang; Linji Gong; Xi Hu; Liang Zhang; et al. (Cell Reports Physical Science, 2021)
Summary: Singlet oxygen (1O2) is extensively employed by reactive oxygen species (ROS)-based cancer therapies, such as photodynamic therapy (PDT) and chemodynamic therapy (CDT). However, the dependences of PDT on light and CDT on complex chemodynamic reactions greatly limit their 1O2-generating efficiencies. Here, we exploit strain and electronic effects to fabricate a bimetallic nanocatalyst by coating a gold nanorod (AuNR) with ~2 platinum (Pt) atomic layers (AuPt0.09), which efficiently generates 1O2 from ground-state oxygen (3O2) by electron-transfer-mediated spin reduction. Density functional theory reveals strain, and electronic effects promote the adsorption of 3O2 onto AuPt0.09, which dramatically enhances 1O2 generation and imparts AuPt0.09, the highest catalytic constant ever reported for 3,3′,5,5′-tetramethylbenzidine oxidation to the best of our knowledge. With a pH-dependent catalytic activity, AuPt0.09 realizes acidity-dependent antitumor effects both in vitro and in vivo, a proof-of-concept demonstration of autocatalytic bimetallic nanocatalyst for light-free oxygen sensitization therapy, which may open a new avenue for 1O2-centered therapeutics.